HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK DENGAN KEKURANGAN ENERGI KRONIK (KEK) PADA REMAJA PUTRI DI SMAN 2 TAMBUN SELATAN TAHUN 2020 - Maya Suryawanti (2020)
Adolescent girls one of the vulnerable groups for nutritional problems. Food consumption and daily physical activity can affect the nutritional status of adolescent girls, nutritional status that is not fulfilled properly can pose a risk to health problems. One of the health problems that occur in adolescent girls is chronic energy deficiency (CED).This research was conducted to analyze the relationship between food consumption and physical activity with chronic energy deficiency (CED) on adolescent girls in SMAN 2 Tambun Selatan in 2020. This research uses a Cross Sectional and done at 204 sample with the sampling method of stratified random sampling. Data collection using questionnaires food consumption and physical activity which has done test Validity and reliability. The results of statistical tests showed there was a significant relationship between eating patterns with chronic energy deficiency (CED) in adolescent girls (p = 0.019). In the physical activity variable, there was no significant relationship with chronic energy deficiency (CED) in adolescent girls (p = 0.179).